Gambaran Resiliensi Pada Remaja Obesitas Yang Mengalami Bullying di Minahasa: Studi Kualitatif - Pinatik, Candiela Criste; Kairupan, B.H Ralph; Buanasari, Andi (Mapalus Nursing Science Journal, 2024)
Background. Bullying in adolescents can harm adolescent psychology, so strong resilience is needed. Purpose. To find out the picture of resilience in obese adolescents who experience bullying. Method. This research uses a qualitative research design with a phenomenological study approach. Selection of participants using purposive sampling techniques, with criteria for obese adolescents who experience bullying. Adolescent participants who experienced bullying were obtained through screening through the distribution of questionnaires on the incidence of verbal bullying. The number of participants was obtained by 12 adolescents, then in-depth interviews and observations were carried out for data collection, then the interview was stopped in the 8th participant because data saturation had been achieved. Result. For the characteristics of participants in this study, the age of each participant aged 13 and 14 years and the length of time participants experienced bullying based on statements from the 8 participants, namely every time they met a friend who bullied, and for participants who lived with parents were all participants. So then obtained 3 themes in this study, namely: 1) The impact of bullying on adolescents, 2) Factors that affect resilience, and 3) Efforts to increase resilience. Discussion. The impact of bullying on adolescents has an impact on the psychology, social, and academic of adolescents, the impact can be seen from changes in behavior, emotions, and others. Conclusion. Most adolescents show good resilience, this is influenced by the motivation and efforts of adolescents to increase resilience. The results of this study can encourage schools and health workers to hold bullying prevention programs. Kata kunci: Resiliensi; Remaja; Obesitas; Bullying